Isolated Striatocapsular Infarcts after Endovascular Treatment of Acute Proximal Middle Cerebral Artery Occlusions: Prevalence, Enabling Factors, and Clinical Outcome - Kaesmacher, Johannes; Huber, Thomas; Lehm, Manuel; Zimmer, Claus; Bernkopf, Kathleen; Wunderlich, Silke; Boeckh-Behrens, Tobias; Manning, Nathan W.; Kleine, Justus F. (Frontiers in Neurology, 2017)
Background: Striatocapsular infarcts (SCIs) are defined as large subcortical infarcts involving the territory of more than one lenticulostriate artery. SCI without concomitant ischemia in the more distal MCA territory (‘isolated SCI’, iSCI) has been described as a rare infarct pattern. The purpose of this study was to assess the incidence of iSCI in patients treated with endovascular thrombectomy (ET), to evaluate baseline and procedural parameters associated with this condition and to describe the clinical course of iSCI patients. Methods: A retrospective analysis of 206 consecutive patients with an isolated middle cerebral artery (MCA) occlusion involving the lenticulostriate arteries and treated with ET, was performed. Baseline patient and procedural characteristics and ischemic involvement of the striatocapsular and distal MCA territory (iSCI, as opposed to non-isolated, SCI, niSCI) were analyzed using multivariate logistic regression models. Incidence of iSCI was assessed and clinical course was determined with the rates of substantial neurological improvement and good functional short- and mid-term outcome (discharge/day-90-mRS ≤2). Results: iSCI was detected in fifty-three patients (25.7%) and niSCI in 153 patients (74.3%). Successful reperfusion (Thrombolysis in Cerebral Infarction, TICI 2b/3) (adjusted Odds Ration, aOR 8.730, 95%-CI 1.069-71.308) and good collaterals (aOR 2.100, 95%-CI 1.119-3.944) were associated with iSCI. In successfully reperfused patients, TICI 3 was found to be an additional factor associated with iSCI (aOR 5.282, 1.759-15.859). Patients with iSCI had higher rates of substantial neurological improvement (71.7% vs. 37.9%, p<0.001) and higher rates of good functional short- and mid-term outcome (58.3% vs 23.7%,p<0.001 and 71.4% vs 41.7%, p<0.001). However, while iSCI patients, in general, had a more favorable outcome, considerable heterogeneity in outcome was observed. Conclusion: High rates of successful reperfusion (TICI 2b/3) and in particular, complete reperfusion (TICI 3) are associated with iSCIs. The high incidence of iSCI in successfully reperfused patients with good collaterals corroborates previous concepts of iSCI pathogenesis. This once considered a rare pattern of cerebral ischemia is likely to increase with the increase in endovascular stroke therapy, which may have implications for patient rehabilitation as well as pathophysiological analyses of isolated ischemic damage confined to subcortical regions within the MCA territory.